PENINGKATAN MOTIVASI BELAJAR FISIKA MELALUI PENERAPAN MODEL PEMBELAJARAN QUANTUM TEACHING DENGAN PENDEKATAN MULTI KECERDASAN DI SMA NEGERI I KAMPAR - Ma’aruf, Zuhdi; Sahal, Muhammad; Susanti, Desi (Jurnal Geliga Sains: Jurnal Pendidikan Fisika, 2007)
The purpose of this research was to find improvement in the student physics learning motivation in teaching physics through applying quantum teaching by multi-intelligence approach implementation by the first-year students at SMA N 1 Kampar in the academic year 2005/2006. Improvement learning motivation is seen 15 learning motivation indicators. The subject of the research is the student X3 class of SMA N 1 Kampar the sample taken was 37 students. The research instrument used to collect data in this research is questioner first motivation and questioner end motivation. The student motivation data analysis by descriptive analysis and differential analysis. The descriptive analysis showed that : (1) The motivation student learning as the topic rectilinear motion through applying quantum teaching by multi-intelligence approach implementation is categorized high and (2) Improvement the student physics learning motivation through applying quantum teaching by multi-intelligence approach implementation 16,2 %.